Axonal regeneration through the fibrous scar in lesioned goldfish spinal cord. (22nd January 2015) - Takeda, A.; Atobe, Y.; Kadota, T.; Goris, R.C.; Funakoshi, K.
Highlights: After spinal injury of goldfish, fibrous scar was formed in the lesion site. Regenerating axons entering the fibrous scar were usually accompanied by glial processes. Regenerating axons pass the fibrous scar through laminin-coated tubular structures. Invasion of glial processes into the tubular structures reduces the fibrous scar area. Regenerating axons increase in parallel with the reduction of fibrous scar area. Abstract: Spontaneous nerve regeneration beyond the scar frequently occurs in fish after spinal cord lesions, in contrast to mammals. Here we examined the spatiotemporal relationship between the fibrous scar and axonal regeneration in the goldfish. Within 1 week after hemisection of the spinal cord, the open wound was closed by a fibrous scar that was demarcated from the surrounding nervous tissue by the glia limitans, which was immunoreactive for laminin. Within 1 week after hemisection, regenerating axons entered the fibrous scar, and were surrounded by laminin-coated tubular structures continuous with the glia limitans. Regenerating axons that initially entered the fibrous scar were usually accompanied by glial processes. Within 2–3 weeks after hemisection, the tubular structures became enlarged, and the regenerating axons increased in number, fasciculating in the tubules. Glial processes immunoreactive for glial fibrillary acid protein and 5-hydroxytryptamine neurons then entered the tubular structures to associate with the regenerating axons. The tubular structures developed further, creating tunnels that penetrated the fibrous scar, through which the regenerating axons passed. At 6–12 weeks after hemisection, the fibrous scar was smaller and the enlarged tunnels contained many glial processes and several axons. The findings of present study demonstrated that, following spinal lesions in goldfish, regenerating axons enter and pass the scar tissue. The regenerating axons first enter the fibrous scar with glial elements and then grow through laminin-coated tubular structures within the fibrous scar. Invasion by glial processes and neuronal elements into the tubular structures reduces the fibrous scar area and allows for more regenerating axons to pass beyond the fibrous scar.